2020
DOI: 10.21203/rs.3.rs-98061/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A gapless unambiguous RNA metagenome-assembled genome sequence of a unique SARS-CoV-2 variant encoding spike S813I and ORF1a A859V substitutions

Abstract: The novel severe acute respiratory syndrome corona virus 2 (SARS-CoV-2) is causing an unprecedented pandemic, threatening global health, daily life, and economy. Genomic surveillance continues to be a critical effort towards tracking the virus and containing its spread, and more genomes from diverse geographical areas and different time points are needed to provide an appropriate representation of the virus evolution. We here report the successful assembly of one single gapless, unambiguous contiguous sequence… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…This in silico study showed that the SARS‐CoV‐2 Nsp3 protein, is critical for the virus replication in cells, 40 is encoded by ORF1a 41 and/or ORF1ab 42 and has similarity to human PARP14 and PARP9. Thus, PARP14 could be depressed by a phenomenon of molecular mimicry causing the polarization of the M1 macrophage phenotype triggering the SARS‐CoV‐2 related cytokine storm by a hyper‐inflammatory state as well as by the MAS.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This in silico study showed that the SARS‐CoV‐2 Nsp3 protein, is critical for the virus replication in cells, 40 is encoded by ORF1a 41 and/or ORF1ab 42 and has similarity to human PARP14 and PARP9. Thus, PARP14 could be depressed by a phenomenon of molecular mimicry causing the polarization of the M1 macrophage phenotype triggering the SARS‐CoV‐2 related cytokine storm by a hyper‐inflammatory state as well as by the MAS.…”
Section: Discussionmentioning
confidence: 91%
“…17 On the other hand, PARP9 is an important molecule that provides protection against lethal viral infections through interferon responses, 39 and as PARP14, also participates in the polarization of macrophages towards the M2 phenotype. 17 T A B L E 2 MHC-I and MHC-II alleles prediction epitopes This in silico study showed that the SARS-CoV-2 Nsp3 protein, is critical for the virus replication in cells, 40 is encoded by ORF1a 41 and/or ORF1ab 42 which is responsible for the SARS-CoV-2 related macrophage activation syndrome, however, the presence of this cytokine produces the decrease of NK and CD8 + T cells, 28,47 a condition found in patients with severe SARS-CoV-2 infections. 28,48,49 This scenario produces in the SARS-CoV-2 patient a state of constant hyper-inflammation, without macrophage immune regulation.…”
Section: Discussionmentioning
confidence: 99%